“PERUMUSAN STRATEGI ORGANISASI KLINIK KECANTIKAN BELLAGREEN SKINCARE KOTA TANGERANG MELALUI PENDEKATAN ANALISIS SWOT” - Herlina Septiani; Arief Budiyanto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract This study aims to explore and analyze the marketing management implemented by the Bellagreen Skincare beauty clinic to increase customer attraction and retention. Amidst increasingly fierce competition in the beauty industry, it is crucial for clinics to understand effective marketing strategies and how customers respond to them. This study employed a qualitative method, employing in-depth interviews with owners, managers, and customers of the Bellagreen Skincare clinic in Tangerang. The results are expected to provide in-depth insights into successful marketing strategies and the challenges clinics face in meeting customer needs and expectations. These findings will contribute to the development of better marketing management practices and effective branding strategies in the beauty industry. Therefore, this research is expected to assist Bellagreen Skincare clinics in designing and implementing more targeted marketing strategies to enhance customer loyalty and overall business performance. Keywords : strategic marketing management, marketing strategy effectiveness, customer loyalty, customer retention, beauty services industry, qualitative approach.